High entropy alloys: Substituting for cobalt in cutting edge technology. (September 2018) - Holmström, Erik; Lizárraga, Raquel; Linder, David; Salmasi, Armin; Wang, Wei; Kaplan, Bartek; Mao, Huahai; Larsson, Henrik; Vitos, Levente
Abstract : Highlights: Metal cutting tools made of cemented carbide are a strong pillar to today's industry. A key ingredient in cemented carbide is cobalt, but it needs to be replaced. Finding a substitution for cobalt is a long-standing problem. We design, produce and test a new cemented carbide with a replacement for Co. The new cemented carbide tool has higher resistance to plastic deformation. Abstract: Cemented carbide, also known as hard metal, is one of the most outstanding composite engineering materials since its commercial introduction in the 1920s. The unique combination of strength, hardness and toughness makes cemented carbides highly versatile materials for the most demanding engineering applications. In their simplest form, these materials are composites of tungsten carbide (WC) grains that are cemented with a ductile metallic binder phase, typically cobalt. However, despite the superiority of Co as binder material, there is a long-standing need to find alternative binders due to serious health concerns that have haunted the industry for nearly 80 years. In the present study, we develop a new cemented carbide with a high entropy alloy binder phase (CoCrFeNi) from raw materials to a fully functional, coated and gradient-sintered cutting tool insert. The new hard metal with reduced Co content is designed by using first principles theory and the CALPHAD method. The cutting tool was made by pressing the new hard metal in a standard geometry, sintered to have a thin binder phase enriched surface zone, free from cubic carbides and coated with protective layers of Ti(C, N) and Al2 O3 . The resulting cutting insert was tested in a real machining operation and compared to a state-of-the-art reference that had Co as binder phase. The cutting tool made of the newly developed cemented carbide has an exceptionally high resistance against plastic deformation at all tested cutting speeds in the machining test, outperforming the reference insert, which shows a linear increase in edge depression when the cutting speed is increased. This result opens up the possibility to utilize the unique properties of high entropy alloys for industrial applications, in particular, as binder phase in new cemented carbides.